An atypical case of neuronal ceroid lipofuscinosis with co-inheritance of a variably penetrant POLG1 mutation - Staropoli John F; Xin Winnie; Barone Rosemary; Cotman Susan L; Sims Katherine B (BMC, 2012)
Abstract Background The neuronal ceroid lipofuscinoses (NCLs, or Batten disease) comprise the most common Mendelian form of childhood-onset neurodegeneration, but the functions of the known underlying gene products remain poorly understood. The clinical heterogeneity of these disorders may shed light on genetic interactors that modify disease onset and progression. Case presentation We describe a proband with congenital hypotonia and an atypical form of infantile-onset, biopsy-proven NCL. Pathologic and molecular work-up of this patient identified CLN5 mutations as well as a mutation-previously described as incompletely penetrant or a variant of unknown significance-in POLG1, a nuclear gene essential for maintenance of mitochondrial DNA (mtDNA) copy number. The congenital presentation of this patient is far earlier than that described for either CLN5 patients or affected carriers of the POLG1 variant (c.1550 G > T, p.Gly517Val). Assessment of relative mtDNA copy number and mitochondrial membrane potential in the proband and control subjects suggested a pathogenic effect of the POLG1 change as well as a possible functional interaction with CLN5 mutations. Conclusions These findings suggest that an incompletely penetrant variant in POLG1 may modify the clinical phenotype in a case of CLN5 and are consistent with emerging evidence of interactions between NCL-related genes and mitochondrial physiology.